2017
DOI: 10.1016/j.jconrel.2017.03.397
|View full text |Cite
|
Sign up to set email alerts
|

BCG vaccine powder-laden and dissolvable microneedle arrays for lesion-free vaccination

Abstract: Live attenuated Bacille Calmette-Guerin (BCG) bacillusis the only licensed vaccine for tuberculosis prevention worldwide to date. It must be delivered intradeemally to be effective, which causes severe skin inflammation and sometimes, permanent scars. To minimize the side effects, we developed a novel microneedle array (MNA) that could deliver live attenuated freeze-dried BCG powder into the epidermis in a painless, lesion-free, and self-applicable fashion. The MNA was fabricated with biocompatible and dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 48 publications
(45 reference statements)
1
45
0
Order By: Relevance
“…8 We used an ablative fractional laser to generate an array of self-renewable microchannels in the skin onto which a patch decorated with an identical pattern of antigen powder dots was aligned, resulting in approximately 80% powder delivery in approximately 1 hour in mouse, human, and pig skin concurrent with little skin irritation. 17,[24][25][26] The powder was retained within the epidermis for an extended period of time, constantly stimulating the immune system for days. [25][26][27] In addition, we identified CpG, an agonist of Toll-like receptor 9 for T H 1 immune responses, and 1,25-dihydroxyvitamin D3 (VD3), an immunosuppressant, to be a potent tolerogenic adjuvant when combined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 We used an ablative fractional laser to generate an array of self-renewable microchannels in the skin onto which a patch decorated with an identical pattern of antigen powder dots was aligned, resulting in approximately 80% powder delivery in approximately 1 hour in mouse, human, and pig skin concurrent with little skin irritation. 17,[24][25][26] The powder was retained within the epidermis for an extended period of time, constantly stimulating the immune system for days. [25][26][27] In addition, we identified CpG, an agonist of Toll-like receptor 9 for T H 1 immune responses, and 1,25-dihydroxyvitamin D3 (VD3), an immunosuppressant, to be a potent tolerogenic adjuvant when combined.…”
mentioning
confidence: 99%
“…17,[24][25][26] The powder was retained within the epidermis for an extended period of time, constantly stimulating the immune system for days. [25][26][27] In addition, we identified CpG, an agonist of Toll-like receptor 9 for T H 1 immune responses, and 1,25-dihydroxyvitamin D3 (VD3), an immunosuppressant, to be a potent tolerogenic adjuvant when combined. 17 To tailor this powder delivery technology for clinical uses, we recently engineered powder-laden, dissolvable microneedle arrays (PLD-MNAs) that could be directly applied onto intact skin to deliver powdered antigens into the epidermis 26 without the need for a laser to perforate the skin.…”
mentioning
confidence: 99%
“…For instance, in one study, the administration of rabies DNA vaccine in dogs using dissolving microneedle patches was reported to be well tolerated in the skin, with mild erythema, minimal wheal formation and a complete resolution of skin reactions within 7 days, without generating any systemic adverse effects [109]. In another study, it was reported that the BCG (Bacille Calmette-Guerin) vaccine powder-laden and dissolvable microneedle arrays displayed similar vaccination efficacy compared to the intradermal (ID) route without incurring significant skin inflammation, whereas the ID vaccination of BCG is known to cause severe inflammation for weeks at the site of inoculation [111].…”
Section: Oralmentioning
confidence: 99%
“…They demonstrated that the delivery of Trp 2/CpG ODN to DCs by mLCPbased VADS elicited a potent systemic immune response to tumors in mice but generated, to later stage B16F10 melanoma, a marginal efficacy, which however, was remarkably boosted through silencing the immune-suppressive cytokine TGF-Ī² in tumor cells with siRNA-loaded LPHa NPs to engender increased tumor infiltrating CD8+ T cells and decreased regulatory T cells within tumor microenvironment. Wu's group fabricated a microneedle array (MA) with HA with a deep cave formed in the basal portion of each microneedle, into which BCG (Bacille Calmette-Guerin bacillus) powder could be packaged directly, thus producing a painless VADS of MA-BCG, which after vaccination by patching on skin of mice caused no overt skin irritation, but elicited strong humoral and cellular immunity comparable to that of intradermal immunization [71]. Notably, other researchers showed in a clinical trial that HA-constructed MA containing trivalent influenza hemagglutinins (A/California/07/2009 (H1N1), A/Victoria/210/2009 (H3N2), and B/Brisbane/60/2008, 15 Ī¼g each) induced immune responses against A/H1N1 and A/H3N2 strains equal to that by subcutaneous injection groups without stirring severe local or systemic adverse reactions and engendered the efficacy against the B strain much stronger than that by the injection group, proving HA-MA a promising practical use as an easy and effective method to replace conventional injection systems [72].…”
Section: Hyaluronic Acid (Ha)-modified Liposomesmentioning
confidence: 99%